Arbuscular mycorrhizal, Mucoromycotina and dark septate fungi in ferns and lycophytes with distribution in Mexico: a global review - Lara-Pérez, Luis Alberto; Zulueta-Rodríguez, Ramón; Andrade-Torres, Antonio (Revista de Biología Tropical, 2017)
Ferns and lycophytes are a group of vascular plants of interest to understand the evolution of mycorrhizal interactions; their preservation is of relevance for their multiple ecological relations. The record of different taxonomic groups of fungi associated with ferns and lycophytes is fragmentary, and the criteria for it identification is inconsistent, which hinders the understanding and determination of mycorrhizal status. The aim of this study was to determine the percentage of the species of ferns and lycophytes with distribution in Mexico, and with information of fungal interactions. A checklist of the presence of arbuscular mycorrhizal fungi (AMF), Mucoromycotina and dark septate fungi (DSF) associated with ferns and lycophytes was integrated through an exhaustive global literature search. In this study, mycorrhizal species was considered by the presence of arbuscules to differentiate with hyphal, vesicular and coils colonization. The study gathered a checklist of mycorrhizal occurrences of 27 families, 61 genus and 137 species of ferns and lycophytes, which covers 13.4 % of the species, 91 % of the genus and 77 % of the families distributed in Mexico. The 78.1 % of the species showed colonization, 56.2 % by AMF, 29.9 % by DSF and 0.72 % by Mucoromycotina fungi. From the total of the species, the higher presences of colonization were in terrestrial, epiphytic, saxicolous, and aquatic plants with 76.6 %, 33.3 %, 20 %, and 6.3 %, respectively. The families of ferns and lycophytes with the higher number of species colonized were Pteridaceae, Polypodiaceae, Aspleniaceae and Dryopteridaceae. The present study showed the widespread associations of AMF and DSF in ferns and lycophytes of Mexico. It is urgently needed to include ferns and lycophytes in studies focused on endomycorhizal interactions, since only 28 species (28 %) were studied in Mexican ecosystems. The majority of studies were focused on sporophytic face (80 %). Nonetheless, to understand the role that plays the mycorrhiza in the establishment of ferns and lycophytes, it is necessary to include the gametophytic face in ecological, molecular and physiological experimental studies. This information is important to implement conservation strategies, because a considerable number of ferns and lycophytes species, depend on these mycorrhizal associations for their growth and survival.